Pengaruh Konsep Diri Guru Pendidikan Agama Kristen Dan Pola Asuh Orang Tua Terhadap Konsep Diri Siswa Kelas VIII SMP Negeri Binaan Khusus Kota Dumai Tahun Pembelajaran 2025/2026 - Meilan Pakpahan; Baginda Sitompul; Justice Zeni Zari Panggabean (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study was to analyze 1) the influence of Christian religious education teachers' self-concept on students' self-concept; 2) the influence of parenting styles on students' self-concept; and 3) the influence of Christian religious education teachers' self-concept and parenting styles together on students' self-concept. The method used in this study is a quantitative research method. The population was all 48 students of Dumai City's Special Guidance State Junior High School in the 2025/2026 Academic Year, and this study was a population study. Instrument trials were conducted on 30 students outside the research sample. Thus, it was found that all research instruments were declared valid and reliable because they had met the validity and reliability criteria. Data were collected using a closed questionnaire consisting of 45 items. The results of the data analysis show that: 1) the F count value > F table is 24.985 > 3.23, thus it is known that there is a positive and significant influence between the self-concept of Christian religious education teachers on the self-concept of class VIII students at Special Guidance State Junior High Schools in the 2025/2026 Academic Year. The influence is 35.2%, 2) the F count value > F table is 27.972 > 3.23, thus it is known that there is a positive and significant influence between parenting patterns on the self-concept of class VIII students at Special Guidance State Junior High Schools in the 2025/2026 Academic Year. The influence is 37.8%, and 3) the calculated F value > F table is 19.053 > 3.23, thus it is known that there is a positive and significant influence between the self-concept of Christian religious education teachers and parenting patterns together on the self-concept of class VIII students at Special Guidance State Junior High Schools in the 2025/2026 Academic Year. The influence is 45.9%, thus Ha is accepted and H0 is rejected.